Sleep Quality Among Medical Students: A Cross-Sectional Study at SRM Medical College and Research Centre - Prasath Thirumalai Raju; Kanimozhi Sadasivam; Sreekumar Ragupathy; K. N. R Aanantha; Kalyanipraba Premsundar; Yuvasri Srinivasan; Saravanan Ayyavoo; Panneerselvam Periasamy (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Sleep quality is crucial for medical students’ academic performance, cognitive function, and mental health. Poor sleep quality is prevalent among medical students, negatively impacting their well-being and future professional competence. Objective: This study assesses sleep quality problems among medical students at SRM Medical College and Research Centre, identifying key demographic factors associated with poor sleep and their potential implications. Methods: A cross-sectional study was conducted with 173 medical students. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and demographic data were analyzed to determine associations using the Chi-square test. Results: The study found that 67.63% of students experienced poor sleep quality (PSQI >5). Sex (χ² = 4.88, P = 0.05) and place of living (χ² = 6.95, P = 0.05) were significantly associated with sleep quality, with 73% of males and 72% of urban students experiencing poor sleep. Other demographic variables, including age, family type, and academic year, showed no statistically significant association with sleep quality. Conclusion: The high prevalence of poor sleep quality among medical students highlights the urgent need for targeted interventions. Strategies such as stress management programs, sleep hygiene education, and institutional policy changes could help improve sleep quality, ultimately enhancing academic performance and future patient care. Further research should explore long-term effects and intervention effectiveness to promote a healthier academic environment.